2017
DOI: 10.1002/eap.1518
|View full text |Cite
|
Sign up to set email alerts
|

Variable effects of climate on forest growth in relation to climate extremes, disturbance, and forest dynamics

Abstract: Changes in the frequency, duration, and severity of climate extremes are forecast to occur under global climate change. The impacts of climate extremes on forest productivity and health remain difficult to predict due to potential interactions with disturbance events and forest dynamics-changes in forest stand composition, density, size and age structure over time. Such interactions may lead to non-linear forest growth responses to climate involving thresholds and lag effects. Understanding how forest dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Recent dieback and mortality of quaking aspen has been well‐documented across its North American range (Michaelian et al, , Worrall et al, ), with studies attributing the tree loss to drought and climatic effects (Worrall et al, ). More recently, studies have shown that the linkage between climate and tree growth is dynamic over time, with periods of increased stress on trees following drought or insect outbreaks (Itter, Finley, D'Amato, Foster, & Bradford, ). Given increasing temperatures and decreasing soil moisture levels at the MEF (Dymond et al, ), plant‐available water levels may drop even further in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Recent dieback and mortality of quaking aspen has been well‐documented across its North American range (Michaelian et al, , Worrall et al, ), with studies attributing the tree loss to drought and climatic effects (Worrall et al, ). More recently, studies have shown that the linkage between climate and tree growth is dynamic over time, with periods of increased stress on trees following drought or insect outbreaks (Itter, Finley, D'Amato, Foster, & Bradford, ). Given increasing temperatures and decreasing soil moisture levels at the MEF (Dymond et al, ), plant‐available water levels may drop even further in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Land use and forest dynamics should be simultaneously considered when projecting forest AGB C uptake across landscapes [5]. Forest AGB C operations should take into account warmer and more variable climates, as well as associated changes of disturbance severity and frequency [70]. Moreover, tremendous forest AGB C stocks still exist that need to be maintained, even as forest AGB C uptake may decrease in the future.…”
Section: How Might We Increase the Forest Agb C Sink In The Northern Us?mentioning
confidence: 99%
“…Severe droughts can lead to declines in tree growth and elevated mortality [24][25][26][27][28][29]. Because tree species often respond in distinct ways to climate, climate change is likely to shift patterns of relative abundance within forests [4,6,26,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Tree growth varies considerably from year to year, and this is often correlated with climatic variations [30]. Studies of annual growth variation in relation to climate are mostly based on dendrochronological (tree ring) data [4,30,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation